Antibiotics Prophylaxis for Implant Surgery in Nigeria - Nathan Ukuoghene Ikimi; Seidu Adebayo Bello; Gloria Okeoghenemaro Agboghoroma; Kolawole Olalekan Obagbemiro (Nigerian Dental Association, 2024)
Abstract Objectives: Bacterial contamination of dental implants during insertion is of serious concern to dental surgeons as it poses significant risk to the success of the procedure. Consequently, routine use of antibiotic prophylaxis during dental implant surgery has been recommended. This study was designed to investigate the use of antibiotics prophylaxis in implant surgery among dentists in Nigeria; to determine the preferred choice, and dosage of antibiotics prophylaxis. Material and Methods: This is a cross-sectional study of dental surgeons prescribing antibiotics prophylaxis for implant surgery in Nigeria. Using Survey Monkey (By Momentive.ai. California, USA) questionnaire investigating choice, dosage and prescription pattern of antibiotic prophylaxis was posted electronically on the WhatsApp Group platforms of the Nigeria Dental Association (NDA) for a period of 3months. Permission to carry out the survey among dental surgeons on the electronic platform was granted by NDA. Data was analyzed with SPSS 25.0 statistics program (SPSS® Inc, Chicago, IL, USA) and statistical significance was set for p≤0.01. Results: Dental Surgeons that returned the completed forms were 72, among which 63.9% prescribed antibiotics prophylaxis. Respondents that administered antibiotics prophylaxis 24hours before surgery were 48.2% and this is statistically significant at p-value 0.266. Clindamycin was the preferred choice of antibiotic for 30.6% and this is statistically significant at p-value 0.743. A 5-day regular dose of Clindamycin 150mg 6hourly beginning 24hours before surgery was practiced by 58.3%. Amoxicillin at 500mg 8hrly for 5 days is the second most commonly used antibiotic prophylaxis.   Conclusion: The result from this study suggests that a high number of respondents were using antibiotics prophylaxis before placing implant, and this is in consonance with studies from other parts of the world. Clindamycin 150mg 6hourly for 5days, beginning 24hours before surgery was the preferred choice.   Key Words: Antibiotics, Contamination, Implant Surgery, Prophylaxis.